Prospects of Using Ferromagnetic Nanoparticles for Cell Cryopreservation - Sukach, A. N.; Grischuk, V. P.; Grischenko, V. I. (Problems of Cryobiology and Cryomedicine, 2008)
Potential possibilities of using ferromagnetic nanoparticles for cryopreservation of cell suspensions have been analyzed. The effect of nanoparticles on low-temperature crystallization of the media of various compositions, as well as the interaction of nanoparticles with cells has been studied. The presence of ferromagnetic (FM) particles in saline and sucrose-containing media has been established to result in the rise of crystallization temperature of the solutions. In addition, the FM particles have been revealed, from one hand, to be bound with cell plasma membrane and, from another, they penetrate into a cell being bound with intracellular structures that potentially may serve as the base for developing novel freezing and thawing protocols for cell suspensions.